2016
DOI: 10.1016/j.celrep.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Selective Maturation of Temporal Dynamics of Intracortical Excitatory Transmission at the Critical Period Onset

Abstract: Although the developmental maturation of cortical inhibitory synapses is known to be a critical factor in gating the onset of critical period (CP) for experience-dependent cortical plasticity, how synaptic transmission dynamics of other cortical synapses are regulated during the transition to CP remains unknown. Here, by systematically examining various intracortical synapses within layer 4 of the mouse visual cortex, we demonstrate that synaptic temporal dynamics of intracortical excitatory synapses on princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 78 publications
6
32
0
Order By: Relevance
“…The increase in connection probability (from P7–8 to P9–11) is prior to the decline in peak amplitude of SST-IN→PC uIPSCs (from P12–13 to P14–15), suggesting that the morphological growth and synapse function are two independent processes. The average probability of SST-IN→PC connections observed (∼58% within 100 µm at P12–20) is lower than previously described with two-photon photostimulation in layer 2/3 of the frontal cortex (∼70% within 200 µm) ( Fino and Yuste, 2011 ) and with paired recordings in layer 2/3 of the visual cortex (∼100% within 100 µm) ( Pfeffer et al, 2013 ), and higher than reported with double or triple patch-clamp recordings in layer 2/3 of the visual cortex (∼20%) ( Thomson and Lamy, 2007 ; Yoshimura and Callaway, 2005 ), in layer 4 of the visual cortex (∼40% at P14–15 and ∼20% at P20–22) ( Miao et al, 2016 ) and in layer 5 of the visual cortex (∼3%) ( Otsuka and Kawaguchi, 2009 ); but agrees with paired recordings in layer 2/3 of the somatosensory cortex (∼63%) ( Xu et al, 2013 ). The discrepancies may be due to regional differences, layer specificity or methodological differences.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The increase in connection probability (from P7–8 to P9–11) is prior to the decline in peak amplitude of SST-IN→PC uIPSCs (from P12–13 to P14–15), suggesting that the morphological growth and synapse function are two independent processes. The average probability of SST-IN→PC connections observed (∼58% within 100 µm at P12–20) is lower than previously described with two-photon photostimulation in layer 2/3 of the frontal cortex (∼70% within 200 µm) ( Fino and Yuste, 2011 ) and with paired recordings in layer 2/3 of the visual cortex (∼100% within 100 µm) ( Pfeffer et al, 2013 ), and higher than reported with double or triple patch-clamp recordings in layer 2/3 of the visual cortex (∼20%) ( Thomson and Lamy, 2007 ; Yoshimura and Callaway, 2005 ), in layer 4 of the visual cortex (∼40% at P14–15 and ∼20% at P20–22) ( Miao et al, 2016 ) and in layer 5 of the visual cortex (∼3%) ( Otsuka and Kawaguchi, 2009 ); but agrees with paired recordings in layer 2/3 of the somatosensory cortex (∼63%) ( Xu et al, 2013 ). The discrepancies may be due to regional differences, layer specificity or methodological differences.…”
Section: Discussionmentioning
confidence: 74%
“…We next examined presynaptic or postsynaptic mechanisms that underlie the differential changes of SST-IN→PC and FS-IN→PC synaptic transmission during eye opening. We assessed the presynaptic release probability by analysis of paired-pulse ratio (PPR), coefficient of variation (C.V.) and failure rate ( Miao et al, 2016 ; Pouzat and Hestrin, 1997 ). In SST-IN→PC synaptic transmission, there were no significant differences in PPR (two-way ANOVA, F (2,132) = 0.172, p = 0.842; Figure 7A and 7B ), C.V. (P12–13, 0.494 ± 0.052, n = 20; P14–15, 0.472 ± 0.052, n = 23; two-tailedunpaired t test, p = 0.775; Figure 7C ) or failure rate (P12–13, 4.8% ± 2.2%, n = 20; P14–15, 5.3% ± 2.8%, n = 23; two-tailed unpaired t test, p = 0.897; Figure 7D ) before and after eye opening at P12–13 and at P14–15.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Sema-3A increases the clustering of pre-and postsynaptic proteins in cortical neurons in vitro [53][54][55][56]. In the context of visual cortical plasticity all these mechanisms could contribute to the experience-dependent selection of inputs onto PV cells, a cellular population that has been shown repeatedly to be involved in regulation of critical periods [15][16][17][18][19][20][21][22]53]. In particular, it has been suggested that one of the early events of the plasticity process activated by monocular deprivation in juvenile mice is pruning of excitatory inputs onto PV cells that would lead to reduced inhibition and increased activation of cortical neurons by stimulation of the open eye.…”
Section: Discussionmentioning
confidence: 99%
“…The precise molecular mechanisms that are responsible for PNNs effect on plasticity remain elusive. The great majority of the PNNs in the visual cortex of rats and mice surrounds parvalbumin (PV) positive neurons [1,14], a class of inhibitory interneurons important for OD plasticity [15][16][17][18][19][20][21][22][23]. A proposed model suggests that the complex structures of PNNs may act as a scaffold by binding plasticity-regulating molecules and by presenting them in high concentration to the neurons they enfold [24].…”
Section: Introductionmentioning
confidence: 99%